USING ENGLISH COMIC AS TEACHING MEDIA TO IMPROVE STUDENT'S READING SKILL AT SMP NEGERI 3 KOMBI - Tampubolon, Gusdian; Tuerah, Ignatius J.; Kumayas, Tirza (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study was to determine how English comics could improve students' reading skill at SMP Negeri 3 Kombi during the school year 2022–2023. The reading test results from the students were utilized to collect the data for this pre-experimental study, which used a one-group pretest-posttest design using a quantitative method. 27 students of SMP Negeri 3 Kombi made up as the study's sample. The results of this study showed a substantial difference between the pre-test and post-test using digital comics, with the post-test mean score increasing by 25.56% to 72.40 from 57.66. The pre-test results showed that 16 (59%) students scored poorly, 9 (33%) performed fairly, and 2 (8%) students scored favorably. While the results obtained in post test classified as fair was 14 (52%) students, good was 9 (29%) students, very good was 4 (15%) students, excellent was 1 (4%) student. Based on these findings, it can be concluded that using comic is effective for improving the reading skill of nineth grade students at SMP Negeri 3 Kombi.